Integrasi Kearifan Lokal dan Kurikulum Pendidikan Islam - Repolinda Repolinda; Jamilah Jamilah; Nur Asikin; Rita Zahara; Yennizar N; Mukhtar Latif (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the integration of local wisdom into the Islamic education curriculum as an effort to create education that is relevant, contextual, and rooted in community culture. Using a descriptive qualitative approach through library research, this study explores the meaning of local wisdom, its relevance to Islamic education, and the models and strategies for its integration into the curriculum. The findings show that local wisdom values such as mutual cooperation, deliberation, and tolerance align with Islamic principles and can be integrated through curriculum planning, experiential learning methods, and the strengthening of the school environment. Several applicable integration models include the local-religious thematic model, the contextual education model, and the integrative-transformative model. Nevertheless, implementation still faces challenges such as teachers' limited understanding, the rigidity of the national curriculum, negative stigma toward certain local cultures, and the scarcity of relevant learning resources. This study recommends teacher training, curriculum policy revision, and cross-stakeholder collaboration to realize a grounded and sustainable Islamic education.